Acrylamide formation and mitigation in processed potato products. - Praegitzer, Sara Marie (Kansas State University, 2011)
Acrylamide is a naturally occurring compound that is formed during the Maillard reaction. The International Agency for Research on Cancer has classified acrylamide as a “probable human carcinogen” as a result of tumor development in laboratory animals when acrylamide is ingested in high concentrations. The amino acid asparagine is particularly important in the formation of acrylamide due to its structural significance; its structure is analogous to that of acrylamide. Potato tubers contain high amounts of asparagine, thus food products such as French fries and potato chips (crisps) have been flagged for their high acrylamide levels and widespread consumption. Acrylamide mitigation in potato products can take place either during raw variety selection (or breeding) or during processing. Heating potatoes at a lower temperature or for a shorter time has shown to significantly decrease acrylamide levels. Numerous studies have shown that use of acidulants, preservatives, and low pH conditions dramatically reduce acrylamide formation by protonation of the asparagine molecule. Hydrolysis and epimerization of sugars during storage, precursor concentrations, and plant physiology are agronomic factors that can be manipulated to decrease acrylamide concentrations. Asparagine has shown to be the rate limiting factor in acrylamide formation, so processing potato cultivars with low asparagine concentrations will result in lower acrylamide levels in the finished product. Continued research areas are focusing on cultivar studies and process optimization to provide a product with lower acrylamide levels but the same sensorial attributes as current products.
Keywords: Acrylamide; Potato; Food Science (0359)